Influence of the Initial Microstructure on the Spheroidization of SAE 52100 Bearing Steel. Issue 1 (27th April 2015) - Hwang, Hoon; De Cooman, Bruno C.
Abstract : High carbon Cr‐bearing SAE 52100 is widely used for bearing production. The in‐service microstructure of bearing steel is tempered high C martensite, which has superior mechanical properties in severe rolling fatigue conditions. The bearings are produced from steel wire with a pearlitic microstructure. Spheroidization annealing is used to obtain a soft microstructure prior to cold deformation. Spheroidization results in a ferritic matrix with coarse globular cementite. The spheroidization annealing process is lengthy, involving considerable economic cost and an environmental impact related to CO2 emissions. Avoiding spheroidization annealing altogether or substantially reducing the annealing time is, therefore, of industrial relevance. Spheroidization annealing may be omitted if a very soft, i.e., coarse pearlitic microstructure, can be obtained after hot rolling. This is generally considered to be the case for a coarse pearlitic microstructure with a hardness of approximately 270 HV. In practice, the requirement for a guaranteed homogeneous low hardness results in the spheroidization annealing being often still necessary in many circumstances. The present work reports on a study of the potential for the reduction of the spheroidization annealing time by spheroidization of different initial microstructures. The two main findings are (i) that the martensitic and bainitic microstructures spheroidize more rapidly than pearlite and (ii) that an initial martensitic microstructure can achieve a hardness lower than 240 HV within 10 h of spheroidization at 710 °C. Abstract : The potential for the reduction of the spheroidization time of SAE 52100 by the spheroidizing of different initial microstructures is analyzed. The two main findings of the study are that the martensitic and bainitic microstructures spheroidize more rapidly than pearlite and that an initial martensitic microstructure can achieve a hardness lower than 240 HV within 10 h of spheroidization at 710 °C.